On the characterization of sandwich panels for solar flat plate collectors’ applications: theoretical and experimental investigation - Djemai, Hocine; Hecini, Mabrouk; Labed, Adnane (Journal of Applied Engineering Science & Technology, 2016)
This paper presents an experimental characterization on the mechanical behaviour of four different sandwich panels, for use in thermal insulation. These Panels are the results of the combination of four composite materials; two materials as skins (Glass-Polyester and Plywood) and two as cores (Polystyrene and Cork agglomerate). From the comparison between the mechanical behaviour of these four sandwich panels which was tested for three point-bending tests; the sandwich with Glass-Polyester as skin and Cork agglomerate as core has the highest overall stiffness compared to the other sandwich panels. Furthermore, thermal characteristics of these four panels (insulation materials) were numerically used in a comparative study of thermal performances of solar flat plate collectors, FPCs. Thus, we have proceeded to the comparison of these FPCs efficiencies in order to determine the best performing model for agro-alimentary drying applications. From the comparison between these four FPCs, the highest efficiency was obtained from the FPC insulation panel with plywood as skin and cork agglomerate as core.
Keywords: Sandwich panels; Flat plate collector; Thermal efficiency; Cork agglomerate; Polystyrene; Overall stiffness